Identifikasi Senyawa Sekunder Ekstrak Metanol Beras Hitam (Oryza sativa L. indica) Organik Dengan Metode Ultrasonik - Umarudin, Umarudin Umarudin (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
information, even though the content of black rice has many benefits, so it is necessary to investigate the early detection of secondary rehabilitate compounds. The purpose of this study was to determine the identification of secondary metabolites contained in organic black rice extract using ultrasonic methods. The method in this study is the true experiment method. This research was tested qualitatively, namely the ultrasonic extraction method and identifying the compounds contained in it, observed for changes in color, sediment, rings, and foam. The research results on determining organic black rice from Tegal, Central Java, are Oryza sativa L. indica. The identification results of organic black rice extract were positive for containing alkaloids, flavonoids, terpenoids, tannins, and saponins and negative for steroid compounds.